Lifestyle and nutrition in stroke prevention - Spence, J. David (Henry Stewart Talks, 2017)
Stroke risk factors overview and management, Mediterranean diet benefits in stroke prevention, Intestinal microbiome and diet effect on atherosclerosis, Dietary recommendations for vascular patients, B Vitamins in stroke prevention